Pendidikan Karakter Pancasila: Sebuah Pendekatan Edukatif di Tengah Disrupsi Teknologi - Bhila, Kanisius; Sampurna, Bonavantura (Sekolah Tinggi Katolik Santo Yakobus Merauke, 2024)
Technological advancement is a current situation that undeniably has brought significant changes to complex human practices. The disruptive impact of technological progress touches all layers, regardless of age, status, or position. In Indonesia, technological disruption is a particular concern for the nation's survival. Indonesian human resources, which are considered still weak, face an unstoppable wave of progress and a flood of information media. This situation leads to issues and dilemmas, with chaotic situations like online gambling, online prostitution, hoaxes, and so on. The conceptual idea developed in this writing aims to delve into the importance of Pancasila character education for the personality development of the Indonesian nation's generation. Pancasila character education is a great force that needs to be cultivated to shape superior, knowledgeable, and characterful Indonesian individuals (students). The fundamental values in Pancasila will provide strength for forming superior, high-quality, democratic, noble, and globally competitive Indonesians.